2006
DOI: 10.1097/01.jsm.0000176372.67398.c8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Creatine Supplementation on Cerebral White Matter in Competitive Sportsmen

Abstract: The results suggest that, for the given dosage regimen, ingested creatine augmentation does not alter the magnetic resonance visible creatine pool in the deep frontal cerebral white matter of young active sportsmen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Oral creatine intake is known to increase brain’s creatine concentration (Dechent et al, 1999). However, accumulation in tissues does not depend only on daily dosing and supplementation duration (Pan and Takahashi, 2007a; Wilkinson et al, 2006). According to the literature, one of the greatest determinants of creatine accumulation in brain after supplementation of creatine is basal creatine level (Pan and Takahashi, 2007b) and the potential for increase in brain’s creatine levels after supplementation is inversely related to its baseline brain levels (Pan and Takahashi, 2007b; Rawson et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Oral creatine intake is known to increase brain’s creatine concentration (Dechent et al, 1999). However, accumulation in tissues does not depend only on daily dosing and supplementation duration (Pan and Takahashi, 2007a; Wilkinson et al, 2006). According to the literature, one of the greatest determinants of creatine accumulation in brain after supplementation of creatine is basal creatine level (Pan and Takahashi, 2007b) and the potential for increase in brain’s creatine levels after supplementation is inversely related to its baseline brain levels (Pan and Takahashi, 2007b; Rawson et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Creatine administration studies in healthy humans, rats and mice have shown no change (Horn et al 1998; Wilkinson et al 2006) or a limited elevation of Cr in the brain (Dechent et al 1999; Ipsiroglu et al 2001; Lyoo et al 2003; Hersch et al 2006) with respect to basal concentrations. Our results show saturation of the cerebral Cr accumulation, which levels off at the normal concentrations of WT control animals.…”
Section: Discussionmentioning
confidence: 99%
“…As discussed, brain creatine content may rely less on exogenous creatine than muscle [20,21,24,28], which could theoretically involve a down-regulated response in brain creatine synthesis upon supplementation. Alternative to this hypothesis is the demonstration that the brain lacks the expression of creatine transporter in the astrocytes involved in the blood-brain barrier, thus implying a limited permeability of the brain to the circulating creatine [29], which is in line with the lack of increase in brain creatine following supplementation reported by some studies [24,28,30]. It is also plausible to speculate that if the brain is, in fact, resistant to exogenous creatine, a highdose, long duration protocol would be needed, such as those used in the study by Dechent et al [27] (i.e., 20 g/day for 4 weeks).…”
Section: The Effects Of Creatine Supplementation On Brain Creatine Lementioning
confidence: 94%